Study of Vehicular and Mobile Internet - Miri, Fulraj; Patel, Rakesh; Patel, Mili (International Journal For Research In Advanced Computer Science And Engineering, 2016)
The first DARPA experiment with wireless mobile internet– ]the Packet Radio Network PRNET–was completely independent the infrastructure. This model was consistent with DARPA military goal sashes PRNET was design support ationsfar away From any wired infrastructure. Beside autonomy, them a in challenge wasmobilityand radioportability.Scarcity of spectrum was not an issue, in ontrast with the ARPANET questtoutilize those 50kbps Telpaktrunks more efficiently. Today, the closest civilian descendants of the PRNET are vehicular networks and smartphone based Personal Area networks. In either case, the wired infrastructure. Moreover, Spectrum scarcity has now become the most important challenge (while, ironically, the Wired Internet has plenty of bandwidth). In this paper we examine this interplay between Wired and wireless and extract a message for the design of amore efficient Future Wireless Internet. We focus on the vehicular networks in ce this field is better establish eland comMetrically more viable than that of personal, P2P communication among Smartphones. We areconfident however that many of our observations will transfer Smartphone infrastructure synergy. Specifically, in this paper we identify the infrastructure role in the support Of emerging vehicular applications and identify the Core Internet service smart chingtheser- Vices inthevehicleg. As the vehicular applications rangefrome -mail and voice over IPto Emergency operations (natural disaster, terrorism attack etc.), the type of assistance Requested from the infrastructure will vary. A shortlist includes: (a)addressing(eg. readdressing) ;(b)directory service, service discovery, mobility management;(c)resource and congestion management; (d) path redundancy;(e)delay tolerant operations; (f) mobileSensor data accessandsear from the internet, and ;(g) anonymity, privacy and incentives. After the review of vehicular applications and properties, we will offer an Internet history Per spectate to help understand how the mobile wireless network fie ldhasevolvedfromthe Early ARPANET and PRNET days .This will revealer end that can helper edict the future of the Wireless Internet.